PENGARUH PENILAIAN PORTOFOLIO TERHADAP KEMAMPUAN MENULIS SISWA SELAMA PEMBELAJARAN DARING - Komang Bela Pradnya Sari; Ni Luh Putu Eka Sulistya Dewi; Ni Putu Era Marsekawati (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
The current study aimed at investigating the effect of portfolio assessment on students’ writing skills during online learning. The study was an experimental study conducted in one selected junior private school in Denpasar. There were 32 students involved in this study. Through pretest and posttest design, the students were introduced to and taught with portfolio assessment. The results of the study confirmed that the students’ pretest score was 73.90 and the posttest score was 76.75. A paired sample t-test conducted confirmed that the mean difference between the pretest and posttest was significant. An effect size test also confirmed that the mean difference between the pretest and posttest was large. Thus, portfolio assessment is encouraged to be applied in the classroom in supporting students’ writing process during online learning.